Perubahan Bentuk dan Dampak Tari Kebagh Terhadap Perkembangan Wisata Daerah Kota Pagar Alam Provinsi Sumatera Selatan - Zeinica, Putri; Citrawati, Anak Agung Istri Agung; Kadir, Ernida; Syofia, Ninon (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the changes in the form and impact of the kebagh Dance on the development of tourism in the Besemah community in Pagar Alam City, South Sumatra Province. The kebagh Dance is a traditional dance of the Besemah community which was originally sacred and functioned in traditional ceremonies, but over time has undergone changes in form, function, and performance context. This study uses a qualitative method with data collection techniques in the form of observation, interviews, documentation, and literature studies. Research informants include artists, studio owners, and community supporters of the Besemah culture. Data analysis focused on changes in elements of the dance performance, such as movement, costume, musical accompaniment, and performance venue, and their impact on the regional tourism sector. This study uses Herbert Spencer’s theory of social change, Y. Sumandiyo Hadi’s theory of dance form, and Soedarsono’s theory of performing arts and tourism. The results show that changes in the form of the kebagh Dance have a positive impact on increasing the cultural tourism appeal of Pagar Alam City, although it has the potential to cause shifts in traditional values and meanings. Therefore, the development of the kebagh Dance needs to be carried out in a balanced manner between preserving cultural values and regional tourism interests.